The mammal type specimens at the Natural History Museum, University of Oslo, Norway - Wiig, Øystein; Bachmann, Lutz (Zootaxa, 2013)
A catalog of mammalian type specimens in the collections of Natural History Museum, University of Oslo, Norway, is presented. All type specimens in the Museum’s mammal collection were revisited and the respective label information was compared with the data provided in the original descriptions. Most taxa were described from type series with no specimen particularly assigned to holotype. The compiled catalog of the type specimens is not intended as a taxonomic revision of the respective taxa, which is why we have not designated lectotypes from the collection’s type series. Specimens that were clearly marked as “the type” in the original description were considered holotypes. The catalog consists of 19 taxa, with the year of authority corrected for three taxa.